2014
DOI: 10.1002/marc.201400578
|View full text |Cite
|
Sign up to set email alerts
|

Design of Smart Oligo(ethylene glycol)-Based Biocompatible Hybrid Microgels Loaded with Magnetic Nanoparticles

Abstract: This article reports a rational strategy for preparing smart oligo(ethylene glycol)-based hybrid microgels loaded with high content of homogeneously distributed preformed magnetic nanoparticles (NPs) (up to 33 wt%). The strategy is based on the synthesis of biocompatible multiresponsive microgels by precipitation copolymerization of di(ethylene glycol) methyl ether methacrylate, oligo(ethylene glycol) methyl ether methacrylate, methacrylic acid, and oligo(ethylene glycol)diac-rylate. An aqueous dispersion of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…A triblock-engineered polypeptide was immobilized on the surface of gold nanorods by electrostatic adsorption. Likewise, Boularas and his research team [153,154] demonstrated the successful formation of microgels with oligoethylenglycol methacrylate (OEG) monomers together with the physical incorporation of Fe 2 O 3 NPs. They were synthesized by conventional precipitation-polymerization and their sizes were approximately 500 nm.…”
Section: Hybrid Nanogelsmentioning
confidence: 99%
“…A triblock-engineered polypeptide was immobilized on the surface of gold nanorods by electrostatic adsorption. Likewise, Boularas and his research team [153,154] demonstrated the successful formation of microgels with oligoethylenglycol methacrylate (OEG) monomers together with the physical incorporation of Fe 2 O 3 NPs. They were synthesized by conventional precipitation-polymerization and their sizes were approximately 500 nm.…”
Section: Hybrid Nanogelsmentioning
confidence: 99%
“…) were prepared by loading preformed MNPs into thermoresponsive oligo(ethylene glycol) methacrylate based nanogels as described by Boularas et al 28 . Briefly, for encapsulating the MNPs into nanogels, the pH of 5 mL of NanoGels solution…”
Section: Encapsulation Of Magnetic Nanoparticles Into Nanogelsmentioning
confidence: 99%
“…Boularas et al 28 Q depends on the degree of crosslinking of polymer matrix and is directly related to the quantity of water that it can be loaded and released by nanogels. The swelling ratio remains the same for non-magnetic nanogels at pH 5.5 and pH 7.5 (Q = 1.7), but it decreases from Q = 3.7 to 1.6 for MagNanoGels-37.5 wt% when the pH increases from 5.5 to 7.5.…”
Section: Synthesis and Characterization Of Magnanogelsmentioning
confidence: 99%
“…Depending on the composition they can be sensitive to external conditions (temperature, pH, magnetic field, light) making them systems of interest for potential applications in numerous fields, namely: drug delivery systems, sensors, catalysis, chemical separation and enzyme immobilization [4][5][6][7][8][9][10][11][12][13]. The swelling/deswelling mechanism of microgels is driven by the free energy changes related to polymer/solvent system and is directly connected to its network elasticity (Flory-Rhener theory) [14,15].…”
Section: Introductionmentioning
confidence: 99%